Immune Modulators as Therapeutic Agents for Cutaneous T-Cell Lymphoma - Rook, Alain H. (2010)
Cutaneous T-cell lymphoma at all stages appears to be responsive to immune modulatory therapeutic approaches. We describe here the mechanistic rationale for the use of interferons, interleukin-12, retinoids, Toll-like receptor agonists, photopheresis and combinations of immune preserving, immune stimulatory therapies for CTCL.